Two new species of Omalodes from Dominican Republic (Coleoptera: Histeridae) - Moura, Daniel P.; Leivas, Fernando W. T.; Caneparo, Maria F. C. (Zootaxa, 2016)
Omalodes Dejean, 1833 is the largest genus of Omalodini, with approximately 63 species described in three subgenera with an exclusively Neotropical distribution. Currently there are only two described species for the Caribbean, both of the subgenus Omalodes, and among other species they are the only ones with complete apical stria on the elytra. Two new species of this subgenus: Omalodes angelo sp. nov. (Holotype male deposited in FSCA: Dominican Republic, Monte Cristi Prov.) and Omalodes kovariki sp. nov. (Holotype male deposited in USNM: Dominican Republic, Monte Cristi Prov.) are described. Both species present a complete apical stria on the elytra and a superficial sulcus or impression on the frons. The lateral pronotal punctures are more evident in O. angelo sp. nov. while in O. kovariki sp. nov. they are weaker, only slightly more evident than the ground punctures. Both species have the punctures of the propygidium somewhat sparse. However, in O. angelo sp. nov. the punctures are limited to the sides and slightly in the middle anteriorly. Omalodes kovariki sp. nov. have a wide glandular opening posterad to metacoxae, a character not registered before for the genus.